Anesthesiologists role in trauma management - Slullitel, Alexandre; Sousa, Angela Maria; Fraga, Adilson de Oliveira (Medicina (Ribeirao Preto), 1999)
The role for the anesthetist in multiprofessional trauma team has increased in the last few years. This paper reviews the role of the specialist concerning the pre-hospital and hospital management extended to the rehabilitation period. Methods of airway management, fluid therapy, monitoring and anesthetic drugs use are discussed. Postoperative analgesia as a way to reduce postoperative morbidity and mortality and reduce hospital stays costs is shown .